Knowledge of the graduants of the Nursing course in the interpretation of blood gasometry in a university center of the interior of Pernambuco (Research, Society and Development, 2020)
The general objective of this study was to evaluate the knowledge of nursing students in a University Center, located in Agreste Pernambucano on the interpretation of blood gas analysis. This is a descriptive study with a quantitative approach. The site of the research was the Unifavip / Wyden University Center. The final sample consisted of 114 nursing undergraduates. For the evaluation, the questionnaire consisted of 16 questions with sociodemographic and study data. Data were analyzed using descriptive statistics through absolute and percentage distributions. The program used to enter data and obtain statistical calculations was the Statistical Package for the Social Sciences (SPSS) version 15. After data analysis, it was found that 77.2% of the students who participated in the survey were female. , 51.8% are between 20 and 25 years old, 75.4% have relationship status, single. It was also possible to show that 62.3% are students enrolled in the ninth period, 58.8% study in the afternoon shift and 82% had already done practical internship. Regarding the collection of arterial blood gas analysis 54.4% had already performed the procedure and 67.5% felt unsafe in the procedure. Finally it was evidenced that a considerable number of minority students could not answer several questions, being specific to the collection and interpretation of arterial blood gas analysis.